1994
DOI: 10.1515/bchm3.1994.375.8.497
|View full text |Cite
|
Sign up to set email alerts
|

Human Protein NEFA, a Novel DNA Binding / EF-Hand / Leucine Zipper Protein. Molecular Cloning and Sequence Analysis of the cDNA, Isolation and Characterization of the Protein.

Abstract: The cDNA libraries constructed from the human acute lymphoblastic leukemia cell line KM3 in the expression vector lambda gt11, were screened with the anti-CALLA (common acute lymphoblastic leukemia antigen) mAb (monoclonal antibody) J5. The selected J5-positive clone I containing a partial cDNA insert was isolated and sequenced. For completing the cDNA sequence the cDNA libraries were further screened by hybridization with the DIG (digoxigenin)-labelled DNA probe derived from clone I, the 5'-end region was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 36 publications
1
84
0
3
Order By: Relevance
“…Moreover, comparison of mRNA levels between cancerous and adjacent non-cancerous tissues by RT -PCR showed that the expression of NUCB2 is downregulated in 50% of gastric tumours. NUCB2 is a Ca 2+ binding protein, which also contains putative DNA binding domain, two helix -loop -helix motifs, EF-hands and leucine zipper (Barnikol-Watanabe et al, 1994;Kroll et al, 1999). It interacts with the postmitotic growth suppressor necdin and is proposed to be involved in the regulation of survival and death of postmitotic cells by controlling Ca 2+ homeostasis in the cytoplasm (Taniguchi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, comparison of mRNA levels between cancerous and adjacent non-cancerous tissues by RT -PCR showed that the expression of NUCB2 is downregulated in 50% of gastric tumours. NUCB2 is a Ca 2+ binding protein, which also contains putative DNA binding domain, two helix -loop -helix motifs, EF-hands and leucine zipper (Barnikol-Watanabe et al, 1994;Kroll et al, 1999). It interacts with the postmitotic growth suppressor necdin and is proposed to be involved in the regulation of survival and death of postmitotic cells by controlling Ca 2+ homeostasis in the cytoplasm (Taniguchi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…All of these interactions presumably occur in the cytoplasm. FIP-3 also appears in the nucleus, where its leucine zipper or zinc-finger domains might promote interactions with the NF-B transcriptional apparatus (43)(44)(45). Recently, while this manuscript was in preparation, the mouse homologue of FIP-3 (named NEMO) was isolated by its ability to complement cells deficient in NF-B .…”
Section: Discussionmentioning
confidence: 99%
“…Nucleobindin was identified in the 1990s as a protein capable of binding Ca 2+ ions, located in the nucleus, the Golgi apparatus, and the endoplasmic reticulum (3,35). Further investigations revealed two types of this protein: nucleobindin-1 (NUCB1) and nucleobindin-2 (NUCB2).…”
Section: Artykuł Przeglądowy Reviewmentioning
confidence: 99%